Essays on Correlation Modelling - Mads Stenbo Nielsen (Copenhagen Business School (CBS), 2011)
The thesis consists of three essays that cover different aspects of correlation modelling in corporate default risk. Each essay is self-contained and can be read independently. Essay I: Correlation in corporate defaults: Contagion or conditional independence? Essay II: Systematic and idiosyncratic default risk in synthetic credit markets. Essay III: Credit spreads across the business cycle.
hdl:10398/8370
Keywords: 650